Occurrence of Mutations in the Antimicrobial Target Genes Related to Levofloxacin, Clarithromycin, and Amoxicillin Resistance in Helicobacter pylori Isolates from Buenos Aires City - Zerbetto De Palma, Gerardo (Microb Drug Resist, 2017)
Domain V of 23S rRNA, gyrA and gyrB Quinolones Resistance-Determining Region (QRDR), and pbp-1A gene point mutations were investigated in Helicobacter pylori-resistant isolates from three centres of Buenos Aires. Minimal inhibitory concentrations (MICs) were performed in 197 isolates from 52 H. pylori-positive naive patients by agar dilution method. Point mutations were achieved by amplification and sequencing of the target genes, and their association with resistance was determined by natural transformation assays. Resistance rates were as follows: metronidazole 28.8%, clarithromycin (CLA) 26.9%, levofloxacin (LEV) 32.7%, and amoxicillin (AMX) 7.6%. Nearly one-third of patients carried multidrug-resistant isolates. A2143G or A2142G in domain V of 23S-rRNA was found in all isolates showing high level of resistance to CLA (MIC >2 mg/L), accounting for 76.0% (38/50) of those with the resistant phenotype. The mutations A2267G or T1861C carried by 8/12 isolates with MIC 1–2 mg/L (low level) did not confer resistance by transformation. Substitutions at GyrA position 87 or 91, mainly N87K and D91G, were found in 92.8% (52/56) of the LEV-resistant isolates: 48 isolates with MIC 4–64 mg/L and 4/8 isolates with MIC 2 mg/L. The remaining four harboured K133N, also present in susceptible isolates. None of the substitutions in GyrB demonstrated to confer resistance. Transformation proved that PBP-1A N562Y and/or T556S substitutions confer the AMX resistance in our isolates, showing an additive effect. In conclusion, the usually reported mutations related to CLA, LEV, and AMX resistance were found in our isolates. However, low-level CLA resistance seems not to be due to mutations in Domain V of 23S rRNA gene.